دور المهارات الناعمة في الأداء الوظيفي دراسة ميدانية في المؤسسة العامة للاتصالات اليمنية - شاوش, زايد ناجي; الأشول, محمـد عبد الله; الزنداني, عبدالله محسن (Journal of Amran University, 2023)
The research aimed to identify the role of soft skills in improving the job performance of employees at the main center of Yemen Telecom (Public Telecom Corporation (PTC) . The analytical descriptive approach was used in the research, a questionnaire was designed specifically for this purpose and the research used a stratified random sample (314) . After analyzing the data using the statistical analysis program (SPSS), The results indicate that there is a positive correlation between the dimensions the soft skills (communication skills, Team work skills, Problem-solving skills, Creativity skills ) and job performance of the employees, The results of the simple regression analysis indicated that soft skills had a statistically significant positive effect on the level of job performance.